Effects of the use of assisted reproductive technologies and an obesogenic environment on resistance artery function and diabetes biomarkers in mice offspring. - Francisco I Ramirez-Perez; Angela L Schenewerk; Katy L Coffman; Christopher Foote; Tieming Ji; Rocio M Rivera; Luis A Martinez-Lemus (PLoS ONE, 2014)
Maternal obesity affects the incidence of cardiovascular disease and diabetes in offspring. Also the use of assisted reproductive technologies (ART) has been associated with cardiovascular deficiencies in offspring. Obese women often suffer from infertility and use ART to achieve a pregnancy, but the combined effects of maternal obesity and ART on cardiovascular health and incidence of diabetes in the offspring is not known. Here, we report the effects of the use of ART within an obesogenic environment, consisting of feeding a western diet (WD) to dams and offspring, on resistance artery function and presence of diabetes biomarkers in juvenile mice offspring. Our results indicate that WD and ART interacted to induce endothelial dysfunction in mesenteric resistance arteries isolated from 7-week-old mice offspring. This was determined by presence of a reduced acetylcholine-induced dilation compared to controls. The arteries from these WD-ART mice also had greater wall cross-sectional areas and wall to lumen ratios indicative of vascular hypertrophic remodeling. Of the diabetes biomarkers measured, only resistin was affected by a WD×ART interaction. Serum resistin was significantly greater in WD-ART offspring compared to controls. Diet and sex effects were observed in other diabetes biomarkers. Our conclusion is that in mice the use of ART within an obesogenic environment interacts to favor the development of endothelial dysfunction in the resistance arteries of juvenile offspring, while having marginal effects on diabetes biomarkers.